2017
DOI: 10.1016/j.neuint.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of SUMOylation in cerebral hypoxia and ischemia

Abstract: The process of protein modification by adding or detaching small ubiquitin-like modifiers (SUMO) proteins, called SUMOylation, contributes to the regulation of numerous processes in eukaryotic cells. SUMOylation also represents a key response and adaption mechanism to different forms of metabolic stress. The central nervous system (CNS) and neurons in particular are highly susceptible to hypoxic-ischemic stress due to the lack of significant oxygen and energy reserves. SUMOylation is observed in many molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 133 publications
0
26
0
1
Order By: Relevance
“…Preventing the accumulation of Aβ in perivascular drainage pathways seems to be a valid therapeutic strategy in AD [16]. It has already been demonstrated that immunotherapy can remove established Aβ plaques from brain parenchyma by 90% [160,161], relieving the restricted diffusion of solutes through the extracellular spaces, ultimately leading to cognitive recovery [129,162]. However, this approach may increase presence of amyloid deposits within the vessel walls, promoting CAA and micro-bleeds [161].…”
Section: Mendelsohn Andmentioning
confidence: 99%
“…Preventing the accumulation of Aβ in perivascular drainage pathways seems to be a valid therapeutic strategy in AD [16]. It has already been demonstrated that immunotherapy can remove established Aβ plaques from brain parenchyma by 90% [160,161], relieving the restricted diffusion of solutes through the extracellular spaces, ultimately leading to cognitive recovery [129,162]. However, this approach may increase presence of amyloid deposits within the vessel walls, promoting CAA and micro-bleeds [161].…”
Section: Mendelsohn Andmentioning
confidence: 99%
“…This is due primarily to our limited understanding of the SUMO-modified proteome involved in brain ischemia. Many recent reviews have speculated on the potential effects on cerebral stroke/ ischemia outcomes of proteins known to be SUMO-targets in general 53,54 ; however, here we wish to focus only on those proteins that have been experimentally demonstrated to be SUMOylated in post-ischemic brains.…”
Section: Sumo Targets In Brain Ischemia/strokementioning
confidence: 99%
“…For example, dynamin-related protein 1 SUMOylation suppresses cytochrome c release and protects the cell from apoptosis (34), whereas hypoxiainducible factor (HIF)-1a SUMOylation may promote HIF-1a degradation and thereby impair HIF-1a-mediated protective effects after ischemia (62). It must be noted that current knowledge with regard to specific SUMO targets involved in brain ischemia is highly limited, and the potential effects of individual SUMOylated proteins within complex pathologies such as brain ischemia are primarily speculative (63).…”
Section: Discussionmentioning
confidence: 99%